The Perbedaan Jumlah Blast pada Hitung Manual dengan Alat Hematologi Siemens Advia 2120i - Mario, Mario; PB, Notopuro (Fakultas Kedokteran Universitas Trisakti, 2023)
Background The development of sophisticated automated blood-cell analyzers caused the proportion of bloodcount samples requiring a manual different count to diminish steadily. Blood smear remains a crucial diagnostic aid in determining the type of leukemia by the appearance and blast numbers in blood smear. Siemens ADVIA 2120i has a parameter of blast cell percentage. This study was undertaken to determine the difference in blast number between manual count and Siemens ADVIA 2120i automatic hematology analyzer. Methods This was an analytical observational study with a cross-sectional design. Thirty samples (22 peripheral blood and eight bone marrow) detected blast numbers from Siemens ADVIA 2120i were examined. Samples were collected from November 2015 to August 2016. A manual count was performed on each sample using a blood smear and bone marrow evaluation. Results Twenty-three cases of AML and 7 cases of ALL were found. Blast percentage from the manual count was between 0 to 95% (Mean 28.5%); from Advia 2120i was between 0.1 to 99% (Mean 16.2%). There was a significant difference in conformity results from blast number between manual count and Siemens ADVIA 2120i with p<0.05. Discussion The difference in blast numbers between manual count and Siemens ADVIA 2120i could be caused by: (1) in manual count, determining blast cells is based on cytoplasm characteristics, granules, nuclear cells, nuclear chromatin, and nucleoli. (2) in ADVIA 2120i, determining blast cell is based on complexity and resistance from BASO reagent. Conclusion Blast numbers were significantly different between manual count and Siemens ADVIA 2120i.